Finite element analysis of mechanical stress of the hip joint in patients with posterior pelvic inclination. (2022) - Sakuma, Daisuke; Ishidou, Yasuhiro; Fujimoto, Yusuke; Nakamura, Shunsuke; Ijuin, Toshiro; Nagano, Satoshi; Taniguchi, Noboru
No abstract available